Jauno vēsturnieku zinātniskie lasījumi, 4 : Starpdisciplināri pētījumi Latvijas vēsturē - (:unkn) unknown (LU Akadēmiskais apgāds, 2019)
Ceturtajā krājumā “Jauno vēsturnieku zinātniskie lasījumi” apkopotie raksti tapuši, paplašinot ziņojumus, kas prezentēti 2018. gada 23. novembrī Valmieras muzejā notikušajā konferencē ar tādu pašu nosaukumu. Konference un tai sekojošs rakstu krājums ir LU Latvijas vēstures institūta (LVI) un Valmieras muzeja ilgstošas un veiksmīgas sadarbības rezultāts. Krājumā publicēti deviņi raksti no 21 konferencē prezentētā referāta, jo vairāki jaunie zinātnieki izvēlējās rakstu neiesniegt, bet daži izstājās, noslēdzoties recenzēšanas procedūrai. Rakstu krājums ir anonīmi recenzēts, to veica nozares speciālisti, zinātņu doktori no Latvijas Universitātes Latvijas vēstures institūta, Vēstures un filozofijas fakultātes un Filozofijas un socioloģijas institūta, kā arī Daugavpils Universitātes, Latvijas Nacionālās bibliotēkas un citām zinātniski pētnieciskām institūcijām. Rakstu krājums “Jauno vēsturnieku zinātniskie lasījumi IV” izstrādāts valsts pētījumu programmas “Latvijas mantojums un nākotnes izaicinājumi valsts ilgtspējai” projekta “Indivīda, sabiedrības un valsts mijiedarbība kopējā Latvijas vēstures procesā: vērtību konflikti un kopīgu vērtību veidošanās vēsturiskos lūzumu punktos” (VPP-IZM-2018/1-0018) ietvaros, un tā izdošanu finansē Latvijas Universitātes Akadēmiskās attīstības projekts un Valmieras muzejs.

Continuing the tradition commenced within the National Research Programme “Letonika”, the already the fourth collection “Scholarly Readings of Young Historians” is reaching its readers. The papers comprised in the present collection have been written on the basis of the reports presented at a conference, which under the same title was held in Valmiera Museum on 23rd November 2018. The conference and the subsequent collection of papers is a result of long-term successful co-operation between the Institute of Latvian History (ILH) and Valmiera Museum. The present volume contains nine papers of the 21 presentations delivered at the conference as several of the young scholars chose not to contribute to the collection while some others withdrew their participation during the reviewing process. The collection is anonymously reviewed by experts of the discipline: doctors of science from the Institute of Latvian History, the Faculty of History and Philosophy and the Institute of Philosophy and Sociology (all under the University of Latvia), Daugavpils University, the National Library of Latvia and other scholarly research institutions. We thank the reviewers for their thorough work that facilitates the growth of the young scholars! The collection “Scholarly Readings of Young Historians IV” has been prepared within the framework of project “Interaction between the individual, the society and the state in process of the history of Latvia: conflicting values and formation of shared values during historical turning points” under the National Research Programme “Latvian Heritage and Future Challenges for the Country’s Sustainability” (VPP-IZM-2018/1-0018) and the publication has been financed by the Academic Development Project of the University of Latvia and by Valmiera Museum.
The Scholarly Readings of Young Historians, 4
Keywords: Jauno vēsturnieku zinātniskie lasījumi; vēsture; arheoloģija